THE INFLUENCE OF RELIGIUSITY, KNOWLEDGE, AND PROFIT SHARING ON STUDENTS’ PREFERENCE ON ISLAMIC BANK - Padang, Kameilina Lora Palik; Junaidi, Junaidi; Antong, Antong (Jurnal Syarikah : Jurnal Ekonomi Islam, 2023)
The low of Islamic bank market share in Indonesia need to uncover which factors to influence consumers’ behaviours and how communication and interaction among Islamic bank and Muslim. This study aims to determine the influence of religion, knowledge and profit sharing on students’ interest in saving in Islamic banks. The population in this study were students at Palopo City University. The number of questionnaires processed in this study were 100 respondents. Structural equation modelling (SEM) was used to examine research hypotheses by AMOS and SPSS software. The results of this study indicate that religiosity has a positive effect on student interest, knowledge has a positive effect on student interest, while profit sharing also has a positive effect on student interest in saving at Islamic banks. It implies Islamic bank managers and regulators need promote the main goals of Islamic bank and systems, which also offers regulations and invite students as agent of change to provide insight among Muslim bank consumers.